2005
DOI: 10.2174/1568026053507688
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in the Development of Selective Small Molecule Inhibitors for Cyclin-Dependent Kinases

Abstract: Loss of normal cell cycle regulation is the hallmark of human cancers, and alteration of the components involved in cell cycle regulation occurs in most human tumors. This suggests that Cyclin dependent kinases (CDKs) are an attractive target for the development of pharmacological agents for the treatment of cancer. Recently, CDK family members that are not directly involved in cell cycle regulation have been identified. This includes CDK7, CDK8, and CDK9, which participate in transcription regulation, and CDK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(34 citation statements)
references
References 60 publications
0
31
0
3
Order By: Relevance
“…Using computational prediction for miR-124a target genes, we observed that CDK6 was one of the best potential targets for miR-124a. CDK6 is involved in cell cycle progression and differentiation (17), and it constitutes an attractive target for the development of anticancer compounds (18). Using CDK6 Western blot analyses, we observed that whereas the original HCT-116 cells with miR-124a methylation-associated silencing strongly expressed CDK6, the cells treated with the demethylating agent or the DKO cells showed CDK6 down-regulation (Fig.…”
Section: Resultsmentioning
confidence: 90%
“…Using computational prediction for miR-124a target genes, we observed that CDK6 was one of the best potential targets for miR-124a. CDK6 is involved in cell cycle progression and differentiation (17), and it constitutes an attractive target for the development of anticancer compounds (18). Using CDK6 Western blot analyses, we observed that whereas the original HCT-116 cells with miR-124a methylation-associated silencing strongly expressed CDK6, the cells treated with the demethylating agent or the DKO cells showed CDK6 down-regulation (Fig.…”
Section: Resultsmentioning
confidence: 90%
“…9,10 All published CDK1 inhibitors are dual CDK1/CDK2, pan-CDK inhibitors, or their cell cycle profiles have been likely affected by off-target activities. 11 The recently published CDK1 inhibitor, RO-3306, appears to have sufficient selectivity to CDK1 vs. CDK2 (>10-fold) and shows an effective G 2 phase block consistent with specific inhibition of its molecular target in the cellular context. 12 Cell cycle analysis revealed that over 95% of the cycling cells from several human cancer cell lines were arrested in G 2 /M phase after treatment with 9 mM RO-3306.…”
mentioning
confidence: 90%
“…This deficiency is due, in part, to the lack of specific molecular tools for reversible modulation of CDK1 activity in vivo. Several potent small-molecule inhibitors have been reported, but their activity and cell cycle profiles are not consistent with specific CDK1 inhibition (9,10). Here, we identify a selective and reversible inhibitor of the catalytic activity of human CDK1͞cyclin B1 and CDK1͞cyclin A complexes that allows synchronization of proliferating cells in the late G 2 phase and probing of CDK1 function in the cellular context.…”
mentioning
confidence: 92%